Exploring Islamic Education in Families to Support Children’s Developmental Tasks in Elementary School - Agisty, Nesha; Rahmat, Munawar; Budiyanti, Nurti (At-Tarbiyat, 2025)
Islamic religious education in the family plays a crucial role in shaping character and supporting children's development, particularly during the elementary school years. This study aims to explore and analyze the role of Islamic religious education in families in supporting the achievement of developmental tasks among elementary school-aged children. The research employs a qualitative method with an exploratory descriptive approach, involving in-depth interviews and participatory observations with six families in Sukajadi District, Bandung, with children aged 6 to 12 years who implement religious education at home. The findings reveal that Islamic religious education in the family significantly contributes to shaping children into individuals who are not only academically intelligent but also morally sound and well-prepared to face life's challenges. Children who receive structured religious education demonstrate strong faith, good character, and high social awareness. This study highlights the importance of designing religious education tailored to children's developmental needs, including daily practice-based learning, moral value instruction, and habitual worship activities. These findings offer practical guidance for parents and educators in integrating Islamic religious education to support children's holistic growth and development. The study also recommends further exploration of the implementation of religious education in broader cultural contexts.